Teachers under the Third Republic in the constant trap of political manipulation - Bogusław Śliwerski (Problemy Wczesnej Edukacji)
In the analysis of the macropolitics of the educational authorities, the author proves that public school teachers find themselves in a situation of a trap that has various faces. During the first years of the political transformation, they experienced the right to professional autonomy and received decent remuneration. They were trusted and respected by politicians for the creative liberation of school education and of institution management from the arrogance and orthodox pressure of the ruling party of the times of real socialism, and together with the systematically regained state power over them, which, as in People’s Poland, systematically since the mid-1990s were reduced them to the level of the precariat and the education and upbringing of young generations enslaved by ideology. We get a picture of the teacher’s state of deformation from freedom to its loss in the fumes of the pretence of care of successive educational authorities for the education of children and youth.